OPG Režek: A Look Into the Future - Burek, Anamarija; Topljak, Danijel; Milinković, Lorena; Stručić, Mihael; Fabijanec, Timon; Uzelac, Zvjezdana (Program održivog razvoja Svete Nedelje, Jastrebarskog i Samobora, 2024)
Family farm Režek is located on the ‘Plešivica Wine Road.’ Upon arrival at the estate, one is pleasantly surprised by the spaciousness, neatness, and the hosts’ hospitality. After touring the property, the researchers realized that the farm’s main weaknesses are product and service promotion and marketing. The first development opportunity is to create a more innovative wine label that will serve as one of the vital promotional elements. Given that the farm is on Wine Road along with several other estates with the same last name, it is also necessary to consider differentiating from other farms. In addition to the winery, they offer accommodations for guests staying overnight. The lodging facilities consist of 10 rooms with a total of 20 beds. The dining hall can host events for up to 80 people indoors and up to 20 people on the terrace. This paper will focus on researching a marketing strategy, showcasing promotion via social media, creating an innovative and attractive label, improving the visibility of signs, and differentiating the farm. We believe these are prerequisites for Family farm Režek to reach end consumers and present its winery in the best possible light.